Effectiveness of In-House Training on Technical Employees in Biotech Industry - Kumar, Amit; Kumar Singh, Sudhir; Kumar, & Govinder (Journal of Technical Education and Training, 2017)
Evaluation and effectiveness of In-house training is the measurement of improvement in the employee’s knowledge, skill and behavioral pattern within the organization as a result of the training program. This measurement helps to design training program for future associated benefits of industrial employees. Thus, it indicates whether the program has been able to deliver its intended goals and objectives. The purpose of this study is to review the training model and to find out the effectiveness of conducted in-house trainings by training department of our organization as Biotech industry. Bharat Immunologicals and Biologicals Corporation Limited is a Biotech industry and located in Bulandshahr city of Uttar Pradesh state in India. The study was conducted with 119 numbers of technical employees; they are actively engaged with production, Quality control and other departments in our organization. Training cycle was adopted according to need in our organization. According to the cycle, six in-house trainings were conducted in our organization and tagged with training code from BTC-001 to BTC-006 in month of January, February, March, April, May and June 2016, respectively. Evaluation and effectiveness of In-house training was determined was assessed for employee performance through questionnaires in pre- and post-assessment and grading system such as grade A, B & C was used to measure the training effectiveness after completion of all the six trainings. Out of 119 technical employees, only 106 participants from production (64 numbers) and quality control (41 numbers) departmental employees of our organization were included in the study for evaluation and effectiveness of the in-house trainings by using grading system. After evaluation of all trainings, We observed that no employee of both departments was placed in grade C and increased the employees number in grade A; 38 numbers instead of 18 in production and 22 numbers instead of 09 from Quality control department. Result of the study shows remarkable impact of all in-house training on the employee’s performance after completion the trainings. Present study is conducted first time in our organization. The training cycle play crucial role to perform in-house trainings for the technical employees in Biotech industry. In-house trainings will be used continuously to nourish the employee skill and have remarkable impact on employee performance.